In silico pharmacological analysis of Tinospora cordifolia compounds targeting African swine fever virus B175L - Kasuni Karunarathne; Saumya Poorni; Nethra Jayampathi; Hasitha Dhananjaya; Anju Hasintha; Malinda Hulugalla; Thilini A.N. Mahakapuge; Nadeeka Nethmini; Naveed Iqbal; Barana Jayawardana; Lakmal Ranathunga (PLoS ONE, 2026)
African swine fever virus (ASFV) is a highly lethal DNA virus that suppresses the host’s immune response by establishing infection. B175L, one of its key immune-evasion proteins, directly inhibits STING-mediated type I interferon (IFN-I) signalling, thereby preventing the activation of antiviral defences. Thus, targeting B175L could be a promising strategy for antiviral drug development as effective ASFV inhibitors remain unidentified. In this study, we investigated the potential of Tinospora cordifolia ’s bioactive compounds to disrupt B175L’s function and restore immune signalling. Gas chromatography-mass spectrometry (GC-MS) analysis of the methanol extract from T. cordifolia stems identified 86 compounds. These were filtered using SwissADME, ProTox 3.0, and DataWarrior, yielding 15 compounds with favourable drug-likeness and safety profiles. We generated a highly accurate 3D model of ASFV B175L with strong confidence scores for the structural accuracy, using AlphaFold3. The filtered compounds were then subjected to virtual screening with PyRx 0.8, and the 3 compounds with binding affinities ≤ −6 kcal/mol were selected for subsequent analysis. Molecular dynamics (MD) simulations were used to assess binding stability, including root mean square deviation and fluctuation (RMSD, RMSF), protein-ligand contacts, radius of gyration (rGyr), and solvent accessible surface area (SASA) using Schrödinger Maestro. Taken together, these in silico results suggest that T. cordifolia- derived Benzaldehyde, 5-bromo-2-hydroxy-, (5-trifluoromethyl-2-pyridyl) hydrazone, Carbamic acid, N-(3-oxo-4-isoxazolidinyl)-, benzyl ester, and 1H-Indol-5-ol may act as potential inhibitors of B175L and represent preliminary antiviral hits against ASFV, warranting further in vitro and in vivo validation.